ANALISIS PEMECAHAN MASALAH PERSAMAAN NILAI MUTLAK SISWA SMA NEGERI 1 PAMONA SELATAN BERDASARKAN LANGKAH POLYA DITINJAU DARI GAYA KOGNITIF: Analysis Of The Absolute Value Equation Problem Solving Of Students Of State Senior High School 1 Pamona Selatan Based On Polya's Steps Reviewed From Cognitive Style - Santika, Putu; Pathuddin; Hasbi, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
The objectives of this research are; (1) to obtain a description of the problem solving of class X MIPA1 students who have the FI cognitive style in solving the absolute value equation at SMA Negeri 1 Pamona Selatan, (2) to obtain a description of the problem solving of class X MIPA1 students who have the FD cognitive style in solving the value equation absolutely in SMA Negeri 1 Pamona Selatan. This type of research is a qualitative descriptive research. The subjects in this study were 2 students taken from 20 students of class X MIPA1 SMA Negeri 1 Pamona Selatan who took the GEFT test. The results of this study indicate that students' problem solving with field independent cognitive style is based on Polya's steps, namely; (1) in understanding the problem, the field independent subject can write down completely what is known and asked in the question correctly, (2) at the planning stage, the field independent subject can relate the things that are known and asked in the question, so that in making problem-solving planning field independent subjects make plans correctly, (3) at the stage of implementing the problem-solving plan field independent subjects can perform calculations properly and correctly, (4) at the stage of rechecking the answers field independent subjects are able to recalculate the answers they get and able to provide conclusions on the answers obtained. The results of student problem solving with field dependent cognitive style are: (1) in understanding the field dependent subject problem can write completely what is known and asked in the question correctly, (2) at the stage of making field dependent subject planning is able to plan problem solving but inaccurate, (3) at the stage of implementing the problem-solving plan, the field dependent subject could not do the calculations correctly, (4) at the stage of re-examining the answers, the field dependent subject did not re-examine the answers obtained and did not provide conclusions on the answers he had obtained. Based on the description above, it can be concluded that the FI subject carried out the four Polya steps in solving the absolute value equation problem solving, in contrast to the FD subject who only performed Polya's three steps in solving the absolute value problem solving.